Spatiotemporal variation of soil heavy metal contamination in urban intersection areas and the vicinity of a former military missile base in Raseiniai district, Lithuania - Usevičiūtė, Luiza; Bradulienė, Jolita (International Conference “Environmental Engineering”, 2026)
The accumulation of heavy metals (HMs) in urban and protected area soils results from multiple anthropogenic emission sources, including vehicular traffic and historical land use. This study aimed at evaluating the levels and risk of HMs contamination in soils around Raseiniai District area, Lithuania. A total of 14 soil composite samples from urban and protected sites were collected at each site in the spring of 2011 and 2018. All investigated sites can be considered potential sources of hazardous pollution, including urban road intersections and the former Bedančiai military missile base, which now belongs to Dubysa regional park. Total concentrations of HMs (Cd, Pb, Cr, Ni, Cu, and Zn) were determined using an atomic flame absorption spectrophotometer. The assessment of HMs contamination in soils and potential ecological threat posed by each HM were conducted following the determination of their concentration levels and multiple contamination and environmental risk indices. Potential ecological risk index (PERI) values ranged from 15.2 to 55.4 in 2011 and from 8.6 to 19.8 in 2018 compared all tested sites, indicating a low ecological risk. Cd and Pb were the dominant contributors as to the total PERI, expressed as Er, in both urban (53.9–69.9% and 22.3–13.2%, respectively) and protected areas (56.0–53.7% and 21.2–19.3%) throughout the entire monitoring period.
Keywords: soil heavy metals; spatial and temporal distribution; urban soil; military sites; contamination indices; potential ecological risk assessment